Adolescentes,tráfico de drogas e medida socioeducativa de internação: um estudo exploratório na região central do estado do Rio Grande do Sul - Welter, Lisiane dos Santos (2021)
Adolescence is a period of great transformations, both at the biological, as well as the social and psychological levels. This period can become of vulnerability, as, crossed by several factors, the adolescent can end up being involved in criminal situations, which when mostly serious, are “punished” with extreme socio-educational measure, hospitalization. Thus, there is a need for studies that seek to understand the phenomena that occur with this public, since serious crimes associated with drug trafficking have increased significantly in recent years. The present study aimed to survey the social, family and personality traits (impulsivity and psychopathy) of adolescents who are being hospitalized in the central region of the state of Rio Grande do Sul for drug trafficking. For the development of the research, the following instruments were used: Mocha and SCID-5 interview (screening instruments), sociodemographic questionnaire, PCL-YV and IMP to assess psychopathic traits and QIAIS to measure impulsivity. The sample consisted of 36 adolescents, and the study had a descriptive-exploratory approach. Among the adolescents, low schooling, frequent use of substances and entry into trafficking were found to be able to meet their needs and have the recognition of their peers. The total of 11.11% of the sample showed psychopathic personality traits and 8.33% of these, more impulsive tendencies. There was no differentiation between the seriousness of the crimes committed by adolescents with psychopathic traits and those that did not exist, nor significant differences regarding social and family issues that were explored.